ANALISIS PENGUNGKAPAN AKUNTANSI LINGKUNGAN, KINERJA LINGKUNGAN DAN BIAYA LINGKUNGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN OIL, GAS & COAL - Arimbi Ika Setyaningrum Arimbi; Sekar Mayangsari (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
With the threat of climate change and a decrease in environmental support. This has led to a paradigm shift in which companies are judged not only based on their company's performance but also on their environmental performance. Regarding the existing phenomena regarding the impact of environmental damage that affects the company's environmental operating activities. Disclosure of environmental accounting is considered to be the best solution to the problems that occur around the company. In addition, by looking at environmental costs and environmental performance, it is expected to support the company. The sample in this study uses Gas, Oil & Coal companies with a timeframe of 2017-2020. The method used in this study is multiple linear regression analysis with the results of research that environmental accounting disclosures do not have an effect on the company, environmental costs, environmental performance have an influence on firm value.